Prescription Behavior of Physicians in the Public and Private Sector - Elina Jussila; Kaisa Kotakorpi; Jouko Verho (Center for Economic Studies and ifo Institute (CESifo), 2022)
We analyze prescription behavior of physicians in the public and private sector. We study two major diseases for which an effective, widely accepted low-cost treatment and alternative, more expensive treatments are available. We find that private sector physicians are more likely to prescribe the expensive medication. The result holds after controlling for individual-level factors including health indicators based on detailed administrative data, and patient fixed effects. In one of our cases, we further find that the same physicians prescribe different medication when working in different sectors. These results are consistent with higher 2nd degree moral hazard in the private sector.
Keywords: I11; H42; I18; 330; healthcare; prescription behaviour; public sector; private sector; moral hazard